1976
DOI: 10.1029/jb081i026p04937
|View full text |Cite
|
Sign up to set email alerts
|

New vertical geodesy

Abstract: Vertical geodesy is undergoing a revolution because of two factors. First, new precise three-dimensional position measurement techniques used over very long distances and based on extraterrestrial reference systems provide a new class and precision of geometric data previously unavailable for geophysical investigations. Second, physical models in tectonic theory for large earthquakes predict crustal distortions that violate the conventional assumptions used to interpret gravity and leveling data. Leveling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 12 publications
(8 reference statements)
0
20
0
4
Order By: Relevance
“…The change in the horizontal component is found to be sufficiently small that the error in measurements of uplift due to errors in level is negligible. Whitcomb [1976] found that error in level led to appreciable errors in uplift in his model. The lack of agreement in our conclusions apparently is due to the differences in the deformation fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the horizontal component is found to be sufficiently small that the error in measurements of uplift due to errors in level is negligible. Whitcomb [1976] found that error in level led to appreciable errors in uplift in his model. The lack of agreement in our conclusions apparently is due to the differences in the deformation fields.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, simple models have been used to get approximate results. In these models [Whitcomb, 1976;Ruff et al, 1976], uplift is simulated by uniformly deforming a cylinder imbedded in the earth's surface; deformation in the cylinder is decoupled from the surrounding rock, which is unstrained. The deformation field in these studies is highly idealized, and so application to real tectonic events is uncertain until results from more realistic models are available for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Anchorage is near the zone of elastic expansion that provided the push for this movement. Whitcomb (1976) showed that density changes can significantly reduce the gravity change expected from elevation changes, and, a few years later, Jachens (1979) published a graph showing that, for elastic expansion and compression with a Poisson's ratio near 0.25, the resulting gravity change could be very small. The gravity data from the Anchorage area thus provides further support for Plafker's hypothesis, which is now a well-accepted aspect of plate tectonics.…”
Section: Anchorage Gravity Changementioning
confidence: 99%
“…However, the agreement was least satisfactory in the negative-elevation-change or subsidence portion of the graph, for which many of the points were acquired after the initial publication. Later studies have refined the analysis of gravity changes and have considered the gravity-change effects of density variation and specific dislocation models (Whitcomb, 1976;Walsh and Rice, 1979;Savage, 1984)…”
Section: Interpretation Principlesmentioning
confidence: 99%
“…These newer systems include the use of modulated light waves (geodimeter), pulsed radio waves (tellurometer), laser ranging to satellites including Moon (Bender Silverberg 1975), radio doppler, and various types of radio and radar altimeters. Recently, radio interferometry employing extra-galactic radio sources, so distant that they behave as fixed points, has been used over very long baselines (Coates et al 1975, Whitcomb 1976.…”
Section: Geodesy and Recent Deformationmentioning
confidence: 99%